pH Sensed interpenetrating polymeric network: Application in drug delivery - Mishra B.; Upadhyay M.; Bakde B. (My University, 2025)
In recent years pH-sensitive interpenetrating polymeric network (IPN) has emerged out as an excellent drug delivery vehicle in controlling the release of numerous therapeutics. Application of ‘smart’, stimuli sensed polymers and the topology of polymeric network of IPN in combination have made this possible. These intelligent delivery systems through mechanism of swelling, extent of cross-linking, concentration of polymeric ratio and change in pH of the environment or media release the entrapped drug at specific time and site in a programmed way. Due to variation in pH in different parts of the body in normal or pathological condition, preparation of such pH sensed IPN could be useful. The literature evidenced development of large numbers of intelligent IPNs with excellent and efficient results. This chapter highlights a brief overview on hydrogel, its translation to smart IPN and its application in delivery of several drugs belonging to the different classes or category. © Springer Nature Singapore Pte Ltd. 2020. All rights reserved.